From neurofilament research to multiple sclerosis clinical practice: Where do we stand?. (28th February 2017) - Bodini, Benedetta; Calabresi, Peter Arthur
Abstract : Neuroaxonal degeneration is a major mechanism underlying clinical progression in multiple sclerosis (MS), but it is incompletely controlled by current therapies and remains challenging to monitor. 1 Neurofilaments (Nf), a major component of the axonal cytoskeleton, are released into body fluids (CSF and subsequently serum) when axonal damage occurs, 2 and therefore have been investigated as promising biomarkers of acute and chronic neuronal damage. In turn, Nf could be an indicator of neuroprotective treatment response in patients with MS. 3, 4 In particular, increased levels of both the light (NfL) and heavy (NfH) subunits in CSF and serum have been found in all stages of MS, with the highest levels reached during clinical and radiologic MRI activity. Previous studies have shown that NfL is associated with acute neuroaxonal damage, while NfH has been correlated with brain volume reduction and clinical disability accrual over time. 5, 6